SIMILARITAS KATA DALAM UDANG-UNDANG DENGAN KAMUS BESAR BAHASA INGGRIS (Information Technology and Telematics, 2015)
Abstract - Since the law is promulgated in the State Gazette, it got binding force. It means that every citizens is bound to acknowledge the Law’s existence. Currently the law is documented in Indonesian and English, but sometimes people could not well understand the text presented in the Law. The word similarity can generate different meaning than the law similarity which is match with english dictionary, to provide an understanding about  government of Indonesia law, especially for foreign countries which has cooperation with Indonesia. This study is to develop law based semantic similarity system using English dictionary, that can be used to provide information about word similarity definition between Law and English dictionary according to user’s need. Similarity is a method to acquire information that is needed by a user from relevant document. This method is usefull to count word similarity weight and produce new definition as output. The data could directly displayed to the user. The information extraction system is made with Java programming language, while for the database is using Microsoft SQL Server 2008 R2. The research produce new defition from weight count between word definition in Law with the definition in English dictionary, based on the user’s need. From the trials conducted, the system success level is seventy percent. Keywords : XML, Java, Semantic Similarity, SQL Server, Law.